Free fatty acid receptors in the endocrine regulation of glucose metabolism: Insight from gastrointestinal-pancreatic-adipose interactions - Zhao, Yu-Feng (Frontiers in Endocrinology, 2022)
Glucose metabolism is primarily controlled by pancreatic hormones, with the coordinated assistance of the hormones from gastrointestine and adipose tissue. Studies have unfolded a sophisticated hormonal gastrointestinal-pancreatic-adipose interaction network, which essentially maintains glucose homeostasis in response to the changes in substrates and nutrients. Free fatty acids (FFAs) are the important substrates that are involved in glucose metabolism. FFAs are able to activate the G-protein coupled membrane receptors including GPR40, GPR120, GPR41 and GPR43, which are specifically expressed in pancreatic islet cells, enteroendocrine cells as well as adipocytes. The activation of FFA receptors regulates the secretion of hormones from pancreas, gastrointestine and adipose tissue to influence glucose metabolism. This review presents the effects of the FFA receptors on glucose metabolism via the hormonal gastrointestinal-pancreatic-adipose interactions and the underlying intracellular mechanisms. Furthermore, the development of therapeutic drugs targeting FFA receptors for the treatment of abnormal glucose metabolism such as type 2 diabetes mellitus is summarized.